What Do We Know about Monetary Policy that Friedman Did Not Know? - Wyplosz, Charles (World Bank, Washington, DC, 2017)
This paper offers a personal review of the current state of knowledge on monetary policy. In a nutshell, what Friedman knew-have survived, but that modern monetary policy departs in some important ways from older principles? The older wisdom that monetary policy determines inflation in the long run but can have systematic shorter run effects has survived a major challenge. Most of the new ideas stem from the recognition of the crucial role of expectations. In today's world, this observation lies behind the spectacular trend toward ever greater central bank transparency. Then it is more than likely that ideas will change in the wake of the global financial crisis. Early debates challenge the old wisdom that central banks ought to be mainly concerned with price stability. In particular, financial stability has always been part of a central bank's mission, but it has occupied limited space in theoretical and empirical studies.